Fatty Acids in the Meat of Buffaloes Supplemented with Fish Oil - Cedres, J.F.; Patiño, E.M.; Judis, M.A.; Negrette, M. Sanchez; Romero, A.M.; Doval, M.M.; Rebak, G.; Crudeli, G.A. (Journal of Buffalo Science, 2013)
The purpose of this study has been to investigate the influence of both a supplementary fish oil diet on conjugated linoleic acid (CLA) and n6 and n3 fatty acids on intramuscular fat in Mediterranean buffalo meat. Twenty animals were randomly divided into two groups and fed with Brachiaria brizantha, 3Kg rice bran, 500 g corn and 500 g sunflower pellets for 60 days. Group I received this diet only while in group II each animal received additional 100 ml fish oil daily. Results indicated a significant decrease of palmitic fatty acid in group II (232.67 mg/g fat) in relation to group I (254.73 mg/g fat). Among unsaturated acids (AGI), the 9c 11t CLA value of group II (21.23 mg/g fat) showed an increase in relation to group I (15.80 mg/g fat), while the linoleic acid content of group II (28,85 mg/g fat) decreased significantly in relation to group I (47,00 mg/g fat). However, the alpha linolenic acid showed no significant difference between the supplemented diet group and the control group (10.31 and 10.70 mg/g fat, respectively). Group II n6/n3 ratio was narrower (2.69:1) than that of group I (4.55:1). Summing up, group II diet, which included fish oil, increased the CLA content in intramuscular fat and decreased the n6 fatty acids, improving the n6/n3 ratio.